The Role of General Practice in Complex Health Care Systems - Schmalstieg-Bahr, Katharina; Popert, Uwe Wolfgang; Scherer, Martin (Frontiers in Medicine, 2021)
According to the WHO, in a complex system “there are so many interacting parts that it is difficult (…), to predict the behavior of the system based on knowledge of its component parts." In countries without General Practitioner (GP)-gatekeeping, the number of possible interactions and therefore the complexity increases. Patients may consult any doctor without contacting their GP. Family Medicine core values, e.g. comprehensive care, and core tasks, e.g. care coordination, might be harder to implement and maintain. How are GPs perceived and perceive themselves if no GP-gatekeeping exists? Does the absence of any GP-gatekeeping influence Family Medicine core values? A PubMed and Cochrane search was performed. The results are summarized in form of a narrative review. Four perspectives regarding the GP´s role were identified. The GPs´ self-perception regarding Family Medicine core values and tasks is independent of their function as gatekeepers, but they appreciate this role. Patient satisfaction is also independent from the health care system. Depending on the acquisition of income, specialist have different opinions of GP-gatekeeping. Policy makers want GPs to play a central role within the health care system, but do not commit to full gatekeeping. GPs and policy makers emphasize the importance of Family Medicine specialty training. Further international studies are needed to determine if Family Medicine core values and tasks can be better accomplished by GP-gatekeeping. Specialty training should be mandatory in all countries to enable GPs to fulfill these values and tasks, and to act as coordinators and / or gatekeepers.